Risk of acute myeloid leukemia and myelodysplastic syndrome after autotransplants for lymphomas and plasma cell myeloma. (November 2018) - Radivoyevitch, Tomas; Dean, Robert M.; Shaw, Bronwen E.; Brazauskas, Ruta; Tecca, Heather R.; Molenaar, Remco J.; Battiwalla, Minoo; Savani, Bipin N.; Flowers, Mary E.D.; Cooke, Kenneth R.; Hamilton, Betty K.; Kalaycio, Matt; et al.
Highlights: TBI conditioning for autotransplantation is associated with higher risks of t-MN. Risks of t-MN after autotransplantation for NHL are increasing. Autotransplantation increases risks of MDS more than AML. Abstract: Background: Exposures to DNA-damaging drugs and ionizing radiations increase risks of acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS). Methods: 9028 recipients of hematopoietic cell autotransplants (1995–2010) for Hodgkin lymphoma (HL; n = 916), non-Hodgkin lymphoma (NHL; n = 3546) and plasma cell myeloma (PCM; n = 4566), reported to the CIBMTR, were analyzed for risk of subsequent AML or MDS. Results: 335 MDS/AML cases were diagnosed posttransplant (3.7%). Variables associated with an increased risk for AML or MDS in multivariate analyses were: (1) conditioning with total body radiation versus chemotherapy alone for HL (HR = 4.0; 95% confidence interval [1.4, 11.6]) and NHL (HR = 2.5 [1.1, 2.5]); (2) ≥3 versus 1 line of chemotherapy for NHL (HR = 1.9 [1.3, 2.8]); and (3) subjects with NHL transplanted in 2005–2010 versus 1995–1999 (HR = 2.1 [1.5, 3.1]). Using Surveillance, Epidemiology and End Results (SEER) data, we found risks for AML/MDS in HL, NHL and PCM to be 5–10 times the background rate. In contrast, relative risks were 10–50 for AML and approximately 100 for MDS in the autotransplant cohort. Conclusions: There are substantial risks of AML and MDS after autotransplants for HL, NHL and PCM.